2010
DOI: 10.1016/j.nlm.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of object recognition but not spatial memory impairment following binge-like alcohol exposure in rats

Abstract: Excessive alcohol use leads to neurodegeneration in several brain structures including the hippocampal dentate gyrus and the entorhinal cortex. Cognitive deficits that result are among the most insidious and debilitating consequences of alcoholism. The object exploration task (OET) provides a sensitive measurement of spatial memory impairment induced by hippocampal and cortical damage. In this study, we examine whether the observed neurotoxicity produced by a 4-day binge ethanol treatment results in long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 52 publications
4
32
1
Order By: Relevance
“…In addition to possible enhancement of hippocampus-dependent learning and memory with low doses of ethanol, studies also showed that prolonged ethanol consumption uniformly resulted in hippocampus-dependent spatial learning deficits (Bond and Di Giusto 1976;Beatty et al 1984;Ehrlich and Humpel 2012), which were shown to be irreversible in some cases (Cippitelli et al 2010). Binge ethanol exposure also results in necrotic cell death and neurodegeneration in the hippocampus (Obernier et al 2002;Hamelink et al 2005).…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%
“…In addition to possible enhancement of hippocampus-dependent learning and memory with low doses of ethanol, studies also showed that prolonged ethanol consumption uniformly resulted in hippocampus-dependent spatial learning deficits (Bond and Di Giusto 1976;Beatty et al 1984;Ehrlich and Humpel 2012), which were shown to be irreversible in some cases (Cippitelli et al 2010). Binge ethanol exposure also results in necrotic cell death and neurodegeneration in the hippocampus (Obernier et al 2002;Hamelink et al 2005).…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%
“…Lesion studies have shown that damage of the hippocampal area mostly produces spatial reference deficits (Jarrard, 1993; Morris et al , 1982) whereas damage of the EC may also compromise reversal learning abilities (Eijkenboom et al , 2000; Hagan et al , 1992). However, cognitive impairment resulting from binge alcohol exposure includes reversal learning and object recognition deficits rather than deficits in acquisition of spatial reference memory in navigation or exploration tasks in rats (Cippitelli et al , 2010a; Cippitelli et al , 2010b; Obernier et al , 2002b). In these studies, re-learning deficits observed in binge alcohol treated animals have been closely associated with different navigation or exploratory patterns reflecting increased perseverative behavior as well as decreased cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Six horizontal sections containing the bilateral hippocampi and the respective EC regions were analyzed for degenerating cells between 5.6 to 6.6 mm ventral from bregma. Cell counting was conducted as previously described (Cippitelli et al , 2010a; Cippitelli et al , 2014; Cippitelli et al , 2010b). Degenerating granule cells of the entire DG were measured using the program Image J (Schneider et al , 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in novel object recognition, or variants of the task, have been observed after repeated exposure to not only meth (Belcher et al, 2007;Gonzalez et al, 2014;O'Dell et al, 2010;Reichel et al, 2014;Reichel et al, 2012b;Rogers et al, 2008), but also cocaine (Briand et al, 2008), ecstasy (Schenk et al, 2010), and alcohol (Cippitelli et al, 2010;Zhao et al, 2012). A few of these studies implicated certain neural mechanisms within a circuit including the prefrontal cortex (Gonzalez et al, 2014;Kamei et al, 2005), hippocampus and entorhinal cortex (Zhao et al, 2012).…”
Section: Novelty Detection Vs Novelty Rewardmentioning
confidence: 99%